2015
DOI: 10.14254/2071-8330.2015/8-1/3
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between wages, labour productivity and unemployment rate in new EU member countries

Abstract: e main aim of this article is to nd out the extent to which relative labour productivity and relative unemployment rate changes determine relative wage changes. We use average annual macro-data for the period 2002-2013 for Poland and other 5 new EU members: Estonia, Hungary, Slovak, Czech Republic and Slovenia. Using Poland as benchmark, rst we examine the correlation between wage, productivity and unemployment rate changes in countries in question. en, using panel data model we assess the elasticities of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…They also notice that gender earning disparities are generally smaller in post-communist countries in comparison to 'old' EU members. The relationship among wages, productivity and unemployment in new EU states is examined by Nikulin (2015). She found that there is no statistically significant correlation between wage and unemployment ratio in the majority of analysed countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They also notice that gender earning disparities are generally smaller in post-communist countries in comparison to 'old' EU members. The relationship among wages, productivity and unemployment in new EU states is examined by Nikulin (2015). She found that there is no statistically significant correlation between wage and unemployment ratio in the majority of analysed countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are several publications focused on different aspects of decent labor remuneration, and their authors contributed to the development of the decent labor remuneration theory: minimum wages ( (Mishchuk, Samoliuk, Bilan, & Streimikiene, 2018); correlations between remuneration, productivity, and unemployment (Nikulin, 2015;Cohen, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This approach allows a researcher to get an idea of the benefits or shortcomings in human capital management strategy. However, contemporary management has moved even further and nowadays it demonstrates at different levels a need not to just improve the human capital, but to consider of the HC components and HR management for achieving the goals of the company (Hayton 2003) or a group of companies (Jagoda 2014), identifying mutual influence of factors and results of the human capital use: for instance, the relations of wages, labour productivity and unemployment (Nikulin 2015). Irrespective of how significant the links at a particular level of empirical research are, theoretical capacity of these hypotheses is beyond any doubt.…”
Section: Making Decisions On Hc Investmentmentioning
confidence: 99%